Characterization of new exopolysaccharide production by Rhizobium tropici during growth on hydrocarbon substrate - Castellane, Tereza Cristina Luque [UNESP]; Campanharo, João Carlos [UNESP]; Colnago, Luiz Alberto; Coutinho, Isabel Duarte; Lopes, Érica Mendes [UNESP]; Lemos, Manoel Victor Franco [UNESP]; de Macedo Lemos, Eliana Gertrudes [UNESP] (Elsevier, 2017)
Exopolysaccharide (EPS) are produced by a diverse of rhizobia species and has been demonstrated to be a bioemulsifier with potential applications in the degradation of hydrocarbons. In the present study, attempts were made to obtain the new exopolysaccharide production by Rhizobium tropici (SEMIA 4080 and MUTZC3) strains during growth on hydrocarbon substrate. Under the different cultivation conditions, the high molecular weight exopolysaccharides from Rhizobium tropici strains cultivated for 96 h mainly consisted of carbohydrates (79–85%) and a low percentage of protein. The EPSC3-D differed from the others, with only 60% of carbohydrate. However, all strains produced polymers with distinct rheology properties, such as viscosity of each EPS sample, suitable for different applications. In addition, RP-HPLC, FTIR and NMR studies revealed EPS produced by rhizobia strains were similar indicating minimal difference between EPS compositions.
Keywords: Bioemulsifier; Exopolysaccharides; Rhizobium tropici